Complexity Analysis of Beat‐to‐Beat Skin‐Surface Laser‐Doppler Flowmetry Signals in Stroke Patients. (July 2015) - Chen, Chao‐Tsung; Hsiu, Hsin; Fan, Jin‐Shiang; Lin, Fong‐Cheng; Liu, Yen‐Ting
Abstract Objectives This study performed skin‐surface LDF measurements and SampEn analysis with the aims of (i) capturing the temporal complexity of cerebral hemodynamics in stroke patients and (ii) discriminating stroke patients from healthy control subjects. We also investigated the response induced by AS in beat‐to‐beat SampEn indexes of LDF signals. Methods LDF signals were obtained at bilateral TaiYang acupoints in 52 stroke patients. Each assessment involved a 20‐minute baseline recording, a 20‐minute AS, and a subsequent 20‐minute recording. The FDT, FRT, and PW were calculated for each pulse of the LDF signals, and then their SampEn values were calculated. Results The SampEn values of FRT were significantly larger in the stroke group (1.064 ± 0.052 and p = 0.013 at the stroke side; 1.059 ± 0.055 and p = 0.017 at the controlateral side) than in the control group (0.975 ± 0.120). On the stroke side, the SampEn of value of FRT was significantly decreased following AS (1.064 ± 0.052 to 1.008 ± 0.060; p = 0.027). Conclusion Larger SampEn values of FRT can be partly attributed to the local regulatory activities that are present in the stroke subjects when facing the induced abnormal vascular conditions and blood flow perfusion resistance. The present findings could aid the development of a noninvasive monitoring technique that will enable discrimination of the different microcirculatory responses in stroke patients.